The night is normal : a guide through spiritual pain - Chole, Alicia Britt (Tyndale Refresh, 2023)
"It's unnerving, isn't it? When our faith feels ungrounded, untethered . . . unreal. When our certainty is adrift, as though an undercurrent has pulled us away from shore into the deep, into the darkness. This is disillusionment. This is spiritual pain. And if this is you, please know that you are not alone. (And you are not as far away from safety as you may feel or fear.) Though faith shines best in full sun, it grows depth in the dark. The night is not your enemy. In fact, the night is necessary. In The Night Is Normal, revered author, speaker, and mentor Dr. Alicia Britt Chole offers a groundbreaking perspective that reveals spiritual disillusionment as an unexpected friend. Within these sacred pages, you'll explore how night-faith develops within your soul something far more satisfying than understanding and far more powerful than peace. Whether you're disillusioned with God, yourself, or others, Alicia offers practical and soul-full tools to help you navigate the night and find your way to a livable and love-saturated hope. Your night will not last forever. Within it, there is priceless treasure (that's simply too weighty to be sourced in sunshine)"--